Different media formulation on biocellulose production by Acetobacter xylinum (0416) - Kamarudin, Suryani; Kalil, Mohd Sahaid; Takrif, Mohd Sobri; Wan Yusoff, Wan Mohtar; Awang Biak, Dayang Radiah; Hasan, Norhasliza (Universiti Putra Malaysia Press, 2013)
Biocellulose (BC), produced by Acetobacter xylinum (0416), was carried out using three types of medium composition under static surface culture. The media used in this experiment included CWHSM (Coconut water in Hestrin-Schramm medium), CM (Complex medium) and HSM (Hestrin-Schramm medium). CWHSM and CM used coconut water from agro-waste as the main source of sugar. The fermentation was conducted for 12 days and the results of BC dry weight, cell entrapped, pH medium and productivity were evaluated and compared. The results show that CWHSM is the most suitable medium for BC production with a productivity of up to 0.044 g l-1 day-1.